Effect of potassium channel blocker Tetraethylammonium pretreatment on prevention of the 6-OHDA-induced chronic Parkinson's disease in rats - H. Haghdoost-Yazdi; S. Sehatbakhsh; M. Sophiabadi; T. Dargahi; MH. Yaghubidust; H. Piri (The Journal of Qazvin University of Medical Sciences, 2016)
Background: Nuclease and caspase activities that promote death signals and cause apoptosis are dependent to potassium ion. Objective: The aim of this study was to investigate the effect of potassium channel blocker tetraethylammonium (TEA) on prevention of Parkinson's disease in rats. Methods: This experimental study was conducted on 33 male rats in Qazvin University of Medical Sciences, 2014. 6-hydroxydopamine (6-OHDA) was injected into the striatum of the brain. The rats received different doses of TEA twice daily the day before the 6-OHDA injection till 15 days after the injection. The severity of Parkinsonism was assessed by the apomorphine-induced rotational behavior, the elevated body swing test (EBST), and the rotarod test. Data were analyzed using Kruskal Wallis and Mann Whitney U tests. Findings: Pretreatment with 5 mg/kg TEA significantly reduced the severity of rotations compared to the saline group. TEA did not reduce the swings in the EBST. In the rotarod test, TEA caused significant improvement in the motor performance of the rats. Conclusion: With regards to the results, it seems that pretreatment with TEA can partly reduce the severity of behavioral symptoms in the 6-OHDA-induced chronic Parkinson's disease. The higher the TEA dose, the more significant the reduction in the severity of symptoms.